Multilingual Code Switching In Contemporary Algerian Occassional Song - Farid Metrouh; Fatma Zohra Mebtouche Nedjai (The Journal of Studies in Language, Culture and Society, 2024)
This study aims to explore and describe the phenomenon of code-switching in contemporary Algerian occasional song that deals with the Coronavirus event, basically to identify the types of code-switching found. Additionally, it investigates the attitudes of Algerian young people towards code-switching in these songs and how it is used as a device to achieve the communicative intents and serve certain functions in songs. To achieve these objectives, the authors relied on a mixed research method that includes twelve selected modern Algerian songs. The analysis was made based on Poplack theory and the six functions of code-switching proposed by Appel and Muysken. To this was added an audience study based on fieldwork in Tizi-Ouzou which involves data collection from survey questionnaires and individual online interviews. Three types of code-switching were discovered. They are extra/intra/ inter sentential code-switching. In addition, the findings show that code-switching in contemporary Algerian song is not a random switch from one code to another, but carries certain social functions that could provoke positive attitudes and behaviors for the target audience.